2006
DOI: 10.1016/j.jcrs.2006.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral ring scotomas following laser in situ keratomileusis

Abstract: A 53-year-old white man who had a history of transient ocular hypertension had bilateral laser in situ keratomileusis (LASIK) for myopia. Subsequent computerized static perimetry revealed bilateral, persistent, repeatable midperipheral ring scotomas. The pre-LASIK visual fields were within normal limits, and the optic discs appeared stable and not diagnostic for glaucomatous optic neuropathy. A comprehensive baseline data set before laser refractive surgery aids subsequent assessment of individuals at high ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…But this number was within the mean parameters [35]. However, there were also some case reports indicated that increased IOP with the microkeratome vacuum ring used during LASIK may have precipitated optic nerve head ischemia and defect of visual field [36, 37]. Meanwhile, a meta-analysis published in ophthalmology showed that there were no statistically significant differences in either visual outcomes or visual quality (contrast sensitivity).…”
Section: Discussionmentioning
confidence: 87%
“…But this number was within the mean parameters [35]. However, there were also some case reports indicated that increased IOP with the microkeratome vacuum ring used during LASIK may have precipitated optic nerve head ischemia and defect of visual field [36, 37]. Meanwhile, a meta-analysis published in ophthalmology showed that there were no statistically significant differences in either visual outcomes or visual quality (contrast sensitivity).…”
Section: Discussionmentioning
confidence: 87%
“…[ 17 18 19 ] On the other hand, tonometry or perimetry are not sensitive enough for detection of early glaucoma. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Five of the 7 patients reported had risk factors for optic neuropathy, such as systemic hypertension, ocular hypertension, coronary artery disease, or a family history of glaucoma. Austin et al 33 were the only authors to conclude that the visual field defect was caused by LASIK-induced aberrations in the cornea due to the appearance of unremarkable discs and a normal peripheral retinal examination.…”
Section: Discussionmentioning
confidence: 99%